Can Digital Activism Change Sustainable Supply Chain Practices in the Agricultural Bioeconomy? Evidence from #Buttergate - Hamish van der Ven (Applied Sciences)
Under what conditions will digital activism elicit a response from industry? What is the nature of that response and how does it impact sustainable supply chain practices? I develop three hypotheses in response to these questions by examining a recent case of digital activism targeted at the use of a controversial bioproduct in the Canadian dairy industry. Drawing on 14 key informant interviews as well as a novel Twitter dataset, I hypothesize that digital activism can elicit a response from industry when it originates with a small number of activists, provided that it also spreads to traditional media. I further hypothesize that industry’s response will be superficial and result in only token changes to sustainable supply chain practices due to the ephemerality and lack of cohesion inherent in some forms of digital activism. These hypotheses lay a foundation for broader cross-sectoral research on how industries respond to digital activism directed at their supply chains and add nuance to ongoing debates about the efficacy of digital activism as a means of changing industry practices.